2016
DOI: 10.4240/wjgs.v8.i10.693
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis: Epidemiology, treatment and outcomes- analysis of 16544 consecutive cases

Abstract: AIMTo investigate the epidemiology, treatment and outcomes of acute appendicitis (AA) in a large population study.METHODSThis is a retrospective cohort study derived from the administrative dataset of the Bergamo district healthcare system (more than 1 million inhabitants) from 1997 to 2013. Data about treatment, surgery, length of stay were collected. Moreover for each patients were registered data about relapse of appendicitis and hospital admission due to intestinal obstruction.RESULTSFrom 1997 to 2013 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 27 publications
5
72
1
6
Order By: Relevance
“…A normal appendix may be found in 14 to 25% of the cases which are operated on the prediagnosis of acute appendicitis (2-4). Its incidence was reported 89/100000 per year (5).…”
Section: Introductionmentioning
confidence: 99%
“…A normal appendix may be found in 14 to 25% of the cases which are operated on the prediagnosis of acute appendicitis (2-4). Its incidence was reported 89/100000 per year (5).…”
Section: Introductionmentioning
confidence: 99%
“…Las publicaciones más recientes refuerzan las conclusiones del estudio y sugieren la adopción de la apendicectomía laparoscópica como estándar de manejo [17][18][19][20] .…”
Section: Discussionunclassified
“…[1][2][3][4][5][6][7] In this study, we analyzed appendectomy timing as a risk factor of complications of appendicitis, especially perforation and SSI. We demonstrated that a delay of more than 12 hours before appendectomy was significantly associated with an increased risk of perforation of the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to prevent potentially significant morbidities, complete surgical excision of the inflamed appendix before rupture is important. [1][2][3][4][5][6][7] Many recent studies have emphasized the importance of preventing appendiceal perforation. In particular, the time interval between hospital visit and surgery is one of the factors that can be objectively quantified and has been analyzed in many prior articles.…”
Section: Introductionmentioning
confidence: 99%